Green Maintenance for Heritage Buildings: An Appraisal Approach for St Paul’s Church in Melaka, Malaysia - Kayan, Brit; Halim, Imaduddin Abdul; Mahmud, Nurush Syahadah (Faculty of Engineering, Universitas Indonesia, 2018)
Maintenance is an important conservation activity in ensuring the survival of heritage buildings for future generations. Knowledge and practices in this field have essentially shifted toward the sustainability framework, comprised of economic, societal, and environmental parameters. Regarding the environment, low carbon repair became the main item on the sustainability agenda for heritage buildings, and this case study supports this growing agenda by examining the "Green Maintenance" concept and methodology. The study aims to determine the applicability of Green Maintenance in assessing low carbon repair for laterite stone structures based on their embodied carbon expenditure, focusing on St Paul's Church within the Historical City of Melaka, Malaysia. In addition, this study highlights the nature of the maintenance and common techniques and materials used in laterite stone repairs. The results reveal that the most sustainable repair techniques are influenced by the longevity of the repair and the embodied carbon expenditure, represented by the Environmental Maintenance Impact (EMI) of Green Maintenance modeling. The EMI measures the amount of "true" CO2 emissions in a sample of laterite-stone-repair techniques over the selected maintenance period, which can be calculated through the "cradle-to-site" boundary of the Life Cycle Assessment (LCA). The study also found that the quality of repair (workmanship), material durability, and selection of materials to deal with specific areas of deterioration are other variables to be considered when determining the most sustainable technique.